The effect of photoperiod on some aspects of reproduction in a Southern African rodent : the pouched mouse (Saccostomus Campestris) - Gray, Janine (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2001)
The pouched mouse, Saccostomus campestris is widely distributed south of the Sahara, inhabiting both subtropical and tropical latitudes and a number of different biotic zones, where it breeds seasonally. In North temperate latitudes, reproduction in small mammals is controlled by photoperiod however this cue becomes less influential as latitude decreases towards the equator. The aim of the present study is to establish the role of photoperiod in the environmental control of reproduction in a seasonally breeding small mammal at low latitudes in a highly unpredictable environment. Spermatogenesis of domesticated and Fl-generation pouched mice was not inhibited by short daylength while decreasing daylength significantly affected the oestrous cycle of adult domesticated female pouched mice. Photoperiod had little effect on the oestrous cycle of F I-generation females while a possible inherent circannual endogenous rhythm controlled inhibition of reproduction in these females. Body mass of male and female juvenile pouched mice was consistently lower in short daylength and in juvenile female pouched mice the onset of fertility may be weight-dependent. The attainment of sexual maturity of domesticated and FIlF2-generation females was retarded but not halted in short daylength and females in long daylength reached puberty 7.8 - 10.2 days earlier. Short daylength also lengthened the interval between vaginal perforation and first oestrus. Puberty in juvenile females was age-dependent as both domesticated and FIlF2-generation males attained puberty at 50 days of age, although fewer males were fertile in long daylength than short daylength. Although litter size of pouched mice was smaller in short daylength for both domesticated and wildcaught females this was not due to a reduction in the ovulation rate. Domesticated females had significantly larger litters than wild-caught females. Male and female pouched mice have evolved different reproductive strategies as males become sexually mature at the same age irrespective of photoperiod and remain fertile throughout the year. In contrast, females tend to be more complex as juveniles delay reproductive maturity and adults become nonreproductive in short daylength. However, in the presence of a fertile male and if environmental conditions are favourable, in short daylength, females can become reproductively active within approximately 3 days. Thus, although the pouched mouse has adopted a purely opportunistic reproductive strategy, vestiges of photoresponsiveness are still present in the female. The seasonality exhibited in the wild is therefore due to the female. Pouched mice live in a highly unpredictable environment so the sole use of photoperiod to regulate reproduction would be disadvantageous.
Keywords: Mice -- Reproduction; Antechinus -- Africa, Southern